Assessing the reactivity of TiCl3 and TiF3 with hydrogen. (2nd August 2018) - Kang, S.; Klebanoff, L.E.; Baker, A.A.; Cowgill, D.F.; Stavila, V.; Lee, J.R.I.; Nielsen, M.H.; Ray, K.G.; Liu, Y.-S.; Wood, B.C.
Abstract: TiCl3 and TiF3 additives are known to facilitate hydrogenation and dehydrogenation in a variety of hydrogen storage materials, yet the associated mechanism remains under debate. Here, experimental and computational studies are reported for the reactivity with hydrogen gas of bulk and ball-milled TiCl3 and TiF3 at the temperatures and pressures for which these additives are observed to accelerate reactions when added to hydrogen storage materials. TiCl3, in either the α or δ polymorphic forms and of varying crystallite size ranging from ∼5 to 95 nm, shows no detectable reaction with prolonged exposure to hydrogen gas at elevated pressures (∼120 bar) and temperatures (up to 200 °C). Similarly, TiF3 with varying crystallite size from ∼4 to 25 nm exhibits no detectable reaction with hydrogen gas. Post-exposure vibrational and electronic structure investigations using Fourier transform infrared spectroscopy and x-ray absorption spectroscopy confirm this analysis. Moreover, there is no significant promotion of H2 dissociation at either interior or exterior surfaces, as demonstrated by H2 /D2 exchange studies on pure TiF3 . The computed energy landscape confirms that dissociative adsorption of H2 on TiF3 surfaces is thermodynamically inhibited. However, Ti-based additives could potentially promote H2 dissociation at interfaces where structural and compositional varieties are expected, or else by way of subsequent chemical transformations. At interfaces, metallic states could be formed intrinsically or extrinsically, possibly enabling hydrogen-coupled electronic transfer by donating electrons.